PENGARUH WHISTLEBLOWING, SPIP, GOOD GOVERNANCE, DAN KOMPETENSI TERHADAP PENCEGAHAN FRAUD DANA DESA - Kadek Sinta Prameswari; Putu Cita Ayu; Ni Putu Trisna Windika Pratiwi (Hita Akuntansi dan Keuangan, 2022)
“Fraud is an act against or violates the law by people from within or from outside the organization, with the intention of obtaining personal or group benefits, directly or indirectly harming other parties. In an effort to minimize the occurrence of fraud, a preventive measure is needed, namely the prevention of fraud. Fraud Prevention is an action or effort to prevent or restrain someone from committing fraud that can be detrimental. This study aims to determine the effect of the whistleblowing system, the government's internal control system, good government governance, and the competence of the village apparatus on preventing fraud in the management of village funds. This research was conducted at the Village Office in East Denpasar District. The sample in this study consisted of 56 village officials. The sampling method used is the saturated method.. The results showed that the variable whistleblowing system, government internal control system, good government governance, and village apparatus competence had a positive and significant effect on preventing fraud in the management of village funds”.